Myocardial Steatosis Is an Independent Predictor of Diastolic Dysfunction in Type 2 Diabetes Mellitus - Rijzewijk, Luuk J.; van der Meer, Rutger W.; Smit, Johannes W.A.; Diamant, Michaela; Bax, Jeroen J.; Hammer, Sebastiaan; Romijn, Johannes A.; de Roos, Albert; Lamb, Hildo J. (Journal of the American College of Cardiology, 2008)
The purpose of this study was to compare myocardial triglyceride content and function between patients with uncomplicated type 2 diabetes mellitus (T2DM) and healthy subjects within the same range of age and body mass index (BMI), and to study the associations between myocardial triglyceride content and function. T2DM is a major risk factor for cardiovascular disease. Increasing evidence is emerging that lipid oversupply to cardiomyocytes plays a role in the development of diabetic cardiomyopathy, by causing lipotoxic injury and myocardial steatosis. Myocardial triglyceride content and myocardial function were measured in 38 T2DM patients and 28 healthy volunteers in the same range of age and BMI by proton magnetic resonance (MR) spectroscopy and MR imaging, respectively. Myocardial triglyceride content was calculated as a percentage relative to the signal of myocardial water. Myocardial triglyceride content was significantly higher in T2DM patients compared with healthy volunteers (0.96 ± 0.07% vs. 0.65 ± 0.05%, p < 0.05). Systolic function did not significantly differ between both groups. Indexes of diastolic function, including the ratio of maximal left ventricular early peak filling rate and the maximal left ventricular atrial peak filling rate (E/A) and E peak deceleration, were significantly impaired in T2DM compared with those in healthy subjects (1.08 ± 0.04 ml/s2 × 10−3 vs. 1.24 ± 0.06 ml/s2 × 10−3 and 3.6 ± 0.2 ml/s2 × 10−3 vs. 4.4 ± 0.3 ml/s2 × 10−3, respectively, p < 0.05). Multivariable analysis indicated that myocardial triglyceride content was associated with E/A and E peak deceleration, independently of diabetic state, age, BMI, heart rate, visceral fat, and diastolic blood pressure. Myocardial triglyceride content is increased in uncomplicated T2DM and is associated with impaired left ventricular diastolic function, independently of age, BMI, heart rate, visceral fat, and diastolic blood pressure.